Nanoparticle loaded implantable flexible microelectrode arrays for pain management after spinal cord surgery - Xu, Nuo (My University, 2021)
The health care system currently faces significant burden with abuse of opioids and an unmet market need for pain management after surgery and injury. A drug delivery device that can improve drug delivery efficiency, increase drug duration of action, and deliver anesthetics topically with low toxicity is needed. Implantable flexible microelectrode arrays are widely used after spinal cord injury for pain mainagement, but they have limitations in improving the solubility, bioavailability, and permeability of drug. Biodegradable polymeric nanoparticles have highly tailorable physicochemical properties, and with incorporation on microelectrode arrays (MEAs), may increase the physical and chemical properties of therapeutic agents such as permeability, solubility and bioavailability. However, drug-loaded biodegradable nanoparticle-polypyrrole coated MEA for drug delivery has not been reported in literature. Therefore, we investigate the use of biodegradable nanoparticles for controlled release of bupivacaine hydrochloride from MAEs for pain management following spinal cord surgery. Bupivacaine hydrochloride, a commonly used FDA-approved anesthetic, is chosen as the model drug due to its nerve block and anti-inflammatory effects. This work starts with the exploration of the relationship between the formulation parameters of biodegradable nanoparticles and their physicochemical properties. Then, the bupivacaine hydrochloride loaded nanoparticles are formulated, and the drug loading of the nanoparticles is explored through iterating formulation parameters. Thereafter, nanoparticles with different surface charges are loaded on the MAEs to determine the relationship between the surface charge of nanoparticles and the release behavior of these nanoparticles. Finally, the release behavior of the nanoparticles from the MAEs is used as a guide to further optimize the bupivacaine hydrochloride loaded nanoparticle formulation.
Thesis (Master's)--University of Washington, 2021
Keywords: Nanotechnology; Chemical engineering